2014
DOI: 10.1037/xap0000002
|View full text |Cite
|
Sign up to set email alerts
|

Effects of speech on proofreading: Can task-engagement manipulations shield against distraction?

Abstract: This article reports 2 experiments that examine techniques to shield against the potentially disruptive effects of task-irrelevant background speech on proofreading. The participants searched for errors in texts that were either normal (i.e., written in Times New Roman font) or altered (i.e., presented either in Haettenschweiler font or in Times New Roman but masked by visual noise) in 2 sound conditions: a silent condition and a condition with background speech. Proofreading for semantic/contextual errors was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
87
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 55 publications
(101 citation statements)
references
References 65 publications
12
87
0
1
Order By: Relevance
“…Furthermore, extending considerably beyond other recent work on auditory distraction (Halin et al, 2014a(Halin et al, , 2014bHughes et al, 2013), we have been able to show that increased task-engagement exerts its impact via a selection process taking place at the point of presentation of distracters rather than later during retrieval processes.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…Furthermore, extending considerably beyond other recent work on auditory distraction (Halin et al, 2014a(Halin et al, , 2014bHughes et al, 2013), we have been able to show that increased task-engagement exerts its impact via a selection process taking place at the point of presentation of distracters rather than later during retrieval processes.…”
Section: Discussionmentioning
confidence: 72%
“…It is worth noting in closing that the shielding effect of increased task-engagement against distraction may have applied as well as the theoretical implications that we have emphasized here: We have now shown that it extends to a variety of applied tasks (proofreading; Halin et al, 2014a;text memory;Halin et al, 2014b) and to a variety of sound-types including acoustically deviant sounds (Hughes et al, 2013) and meaningful speech (present DYNAMIC COGNITIVE CONTROL OF IRRELEVANT SOUND 31 study; Halin et al, 2014a;2014b). Whilst no doubt counterintuitive, degrading visual stimuli may have value as a practical intervention for individuals with poor attentional control such as those with cognitive deficits characterising schizophrenia (Cellard, Tremblay, Lehoux, & Roy, 2007), normal ageing (e.g., Hasher & Zacks, 1988), dementia of the Azheimer's type (Levinoff, Li, Murtha, & Cherktow, 2004) and attentional deficit hyperactivity disorder (Pelletier, Hodgetts, Lafluer, Vincent, & Tremblay, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, background speech tends to impair tasks like proofreading (Halin et al, 2013), reading comprehension (Halin et al, 2014;Perham and Currie, 2014), and writing (Keus van de Poll et al, 2014;S€ orqvist et al, 2012) that are presumably representative of the type of task typically undertaken in office environments. Many companies have introduced masking sound in the working environment to combat the potential negative impact of background speech on such cognitive tasks.…”
Section: Introductionmentioning
confidence: 99%